Kontribusi Pendapatan Perempuan Buruh Tani Pisang terhadap Pendapatan Keluarga di Kecamatan Padang Tiji Kabupaten Pidie - Sofyan Sofyan; Nita Sari Tarigan (Jurnal Agrisep, 2013)
ABSTRACT. The study entitled "Womens Contribution of the Banana Worker Womens Family Income in the District of Padang Tiji, Pidie." There are two problems in this study, that is: 1) How much money can women earn as a peasant in the women of farm workers family in the District of Padang Tiji, Pidie? and 2) How large is the revenue contribution of women of farm workers in the banana farming to monthly household income in the district of Padang Tiji, Pidie? The aim of this study is 1) To know much money can women earn as a peasant in the women farm workers family in the District of Padang Tiji, Pidie and 2) To determine how is the revenue contribution of women farm workers in the banana farming to monthly household income in the district of Padang Tiji, Pidie. The population of this study were 282 women farm worker women, with a total sample of 28 respondents or 10 % of the total population. The results showed that: 1) The average income of farm workers women of banana farm in the district of Padang Tiji is about Rp.787.500,- while 2) The contribution income of farm workers women banana farming is one of the biggest income besides husband's income in a family, which is in line with the level of the percentage income of women up to 30 % of total family income.